Exercise acutely increases vitamin D receptor expression in T lymphocytes in vitamin D‐deficient men, independent of age. Issue 7 (19th May 2021) - Lithgow, Hannah; Florida‐James, Geraint; Ross, Mark; Duncan, Gary; Leggate, Melanie
Abstract : New Findings: What is the central question of this study? Does exercise affect vitamin D receptor expression in T lymphocytes in young, middle‐aged and older adults? What is the main finding and its importance? Moderate‐intensity cycling exercise increases vitamin D receptor expression in vitamin D‐deficient men, independent of age, presenting a strategy to combat the prevalence of vitamin D deficiency. Abstract: Vitamin D plays a key role in the modulation of the immune system, mediated through the intracellular vitamin D receptor (VDR). Exercise has been shown to influence the activity and availability of the VDR. The aim of this study was to investigate the effect of age on basal immune cell (T‐lymphocyte) VDR expression and the subsequent effect of acute aerobic exercise to modulate VDR expression in peripheral T cells. Thirty‐five men were included in the study (mean ± SD: age 44 ± 17 years and body mass index 25.7 ± 3.1 kg/m 2 ), separated into three age groups: 18–30 ( n = 12), 31–45 ( n = 11) and 60–75 years ( n = 12). Participants completed two trials [control (CON) and aerobic exercise (AE)], with blood samples collected pre‐ and postexercise (0, 1 and 3 h). Peripheral blood T cells were isolated and analysed for VDR expression by flow cytometry. The results show that advanced age is associated with lower VDR expression in T cells (882 ± 274, 796 ± 243 and 594 ± 174 geomean in the 18–30, 31–45 and 60–75 year age groups, respectively). Acute AE was successful at acutely increasing VDR expression in T cells, irrespective of age. Advanced age corresponds to a lower T‐cell VDR expression, which might be responsible for age‐associated development of chronic conditions and autoimmunity. Exercise was successful in increasing VDR expression in T cells irrespective of age and independent of exercise‐induced T‐cell mobilization. Abstract :